Implementasi Relokasi Pasar Youtefa di Kota Jayapura - Awi, Robert L. N.; Silo, Akbar; Z Kaiwai, Hans (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2024)
The purpose of this research is to find out and describe the implementation of Youtefa market relocation in Jayapura City and to find out the obstacles in the implementation of Youtefa traditional market relocation in Jayapura City. This research was conducted at the Office of Industry Trade Cooperatives and Small and Medium Enterprises. This type of research is qualitative which is descriptive. Primary data is collected directly from the field. Primary data sources are data sources that can directly provide information about anything related to the problem under study. Secondary data archives, papers, scientific journals, literature, laws and regulations, documents from related parties, and books related to the research problems of data structuring are analyzed using descriptive methods. The author uses triangulation to verify the truth of the collected data. The results of the research on the implementation of Youtefa market relocation policy show that in communication, the efforts made by the government to implement this policy are seminars, directives from the mayor of Jayapura, internal staff meetings, staff coordination. The number of policy implementers involved is sufficient. The employees who also act as implementers have a good attitude towards the policy. There is no SOP as guidelines and implementation instructions.